HUBUNGAN TRAVEL CONSTRAIN DAN CITRA DESTINASI TERHADAP LOYALITAS WISATAWAN DI WILAYAH KABUPATEN BOGOR BAGIAN BARAT - Edwin Aldrianto; Bambang Juanda; Sri Mulatsih; Ernan Rustiadi (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
This study aims to analyze the structural relationship between travel constraints and destination image on tourist loyalty. This was conducted in July-August 2019 in Tenjolaya Subdistrict and Pamijahan Subdistrict. The analysis using the PLS SEM method gives the result that the X3 construct (travel constraint) has a significant negative effect (-0.443) in influencing the X8 construct (visitor loyalty) as reflected in the interest in returning visits. This negative value is greater than the structural effect of the X4 construct (sense of place) which is only 0.390. It can be concluded that the destination that only relies on natural conditions has no significant effect on tourists' interest in making return visits if they have traveling constrain to the site. Keywords: destination, rural, tourism, travel constraints